Innovative Technologies in Methodology of Teaching English at The University - Ibrohimova Lobar Ishokovna (Genius Journals, 2021)
Article considers about methods of teaching English at high schools. The progress and principal changes of the methods of the study of the language, certainly, are connected with novation in the field of psychologies of the personalities and groups. As well as there is analyzed the traditional and innovative methods of the foreign language teaching.
Keywords: Innovative Methods; Methods of Teaching; Fundamental Methods; Classical Approach